1992
DOI: 10.1038/sc.1992.150
|View full text |Cite
|
Sign up to set email alerts
|

Bladder rehabilitation with dorsal rhizotomy and ventral neuroprosthesis

Abstract: Two patients with severe neuropathic bladders were successfully treated with selective dorsal rhizotomy in conjunction with a ventral root neuroprosthesis. Both patients achieved stabilization of their renal function, continence, resolu tion of vesicoureteral reflux, and relief from indwelling urethral catheters. This alternative form of management avoids the complications of other operative approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Manipulation of S3 activity has been employed effectively for facilitating bladder storage. Sacral rhizotomy, for example, serves to interrupt the voiding reflex arc, reducing filling pressures, and increasing the functional bladder capacity [Gasparini et al, 1992;Baskin and Schmidt, 1992]. Electrical modulation of bladder function has also been employed with reported success [Dijkema et al, 1993;Bosch and Groen, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of S3 activity has been employed effectively for facilitating bladder storage. Sacral rhizotomy, for example, serves to interrupt the voiding reflex arc, reducing filling pressures, and increasing the functional bladder capacity [Gasparini et al, 1992;Baskin and Schmidt, 1992]. Electrical modulation of bladder function has also been employed with reported success [Dijkema et al, 1993;Bosch and Groen, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of S3 activity is an effective treatment for bladder overactivity [10]. Sacral rhizotomy interrupts the voiding pathway, with reported success [11, 12]. Electrical modulation of voiding has been most effective when applied invasively by the implantation of sacral nerve stimulators [13].…”
Section: Discussionmentioning
confidence: 99%
“…For instance in Tanagho et al's original canine experiments (when continuous stimulation was used) it was concluded that stimulation frequencies of 20–30 Hz represented a trade‐off between urethral sphincter muscle fatigue and force of contraction. It is thus unclear why his original collaborator (Schmidt) later used a continuous train of pulses with a frequency of 15 Hz to take forward into humans with paraplegia [65].…”
Section: Discussionmentioning
confidence: 99%